A sport-for-protection program reduces suicidal ideation in youth affected by displacement: a secondary analysis of the Game Connect trial in Uganda - Latimer, Kathleen; Larok, Rita; Nyeko, John Paul; Lukungu, Bashir; Rosenbaum, Simon; Murungi, Lydia; Nannungi, Robinah; Carrin, Jeroen; Kalule, Esther Nanfuka; Luwangula, Ronald; Vancampfort, Davy (Frontiers in Psychiatry, 2025)
IntroductionDisplaced youth face numerous stressors and are at high risk of experiencing suicidal ideation. Sport-for-protection programs offer a potentially effective strategy to reduce this risk; however, randomized controlled trials (RCTs) evaluating interventions in displacement contexts are lacking.MethodsDisplaced youth and youth from host communities in five humanitarian settings across Uganda, aged 15 to 24 years, with at least mild symptoms of anxiety and/or depression and suicidal ideation, were randomized to a 13-session sport-for-protection program or a wait-list control. The Generalized Anxiety Disorder-7 (GAD-7) and Patient Health Questionnaire-9, adolescent version (PHQ-9-A) were assessed pre- and post-intervention. Logistic and linear regression modeling were conducted.ResultsIn total, 542 of 817 young people (66.3%) reported suicidal ideation (PHQ-9-A ≥1) in the past 2 weeks. Of these 542, 277 were randomized to the experimental group and 265 to the control group. The median age was 19.0 years, 45.6% were boys, 13.1% had a self-reported or observed disability, 25.8% were from host communities, and 74.2% were displaced youth. The prevalence of suicidal ideation dropped to 11.5% following the sport-for-protection intervention, compared to 53.2% in the control group (Cohen’s h = 0.94, P<0.001, indicating a large difference; odds ratio for no suicidal ideation following sport-for-protection vs the control condition = 8.7, 95% confidence interval = 5.6-13.5).ConclusionSport-for-protection is an effective stand-alone or adjunctive intervention to reduce suicidal ideation among young people affected by displacement in humanitarian settings.